Evaluation of Quality of life, Physical Activity and Nutritional Profile of Postmenopausal Women with and without Vitamin D Deficiency - Delchiaro, Adriele; Oliveira, Flávia de Jesus; Bonacordi, Camila Lopez; Chedid, Bruna Libanori; Annicchino, Giuliana; Fernandes, Cesar Eduardo; Strufaldi, Rodolfo; Pompei, Luciano M.; Steiner, Marcelo Luis (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Introduction Vitamin D deficiency is associated with various diseases. Prevalent in Brazil, it can result from inadequate lifestyle habits.Objective To demonstrate that postmenopausal women with vitamin D deficiency have worse quality of health, expressed as worse quality of life, lower levels of physical activity, and worse nutritional profile.Methods Postmenopausal women answered questionnaires about physical activity and quality of life, provided a 24-hour food record, and had serum vitamin D levels measured.Results Among the more active women, those who perform a daily average of one hour of physical activity had vitamin D levels above 20 ng/mL (76.9%), and those, which expose themselves to sunlight, had vitamin D levels above 30 ng/mL (34.6%). Meanwhile the percentages for the women who are less physically active and less exposed to sunlight were 42.2% and 8.9% respectively. Being more active and more exposed to sunlight resulted in a lower fat percentage. Serum vitamin D levels were not correlated with quality of life.Conclusion Walking and gardening increased serum vitamin D levels and decreased the percentage of body fat. The limitations of the study prevented the impact of 25-hidroxyvitamin D on the quality of life and nutritional aspects of the women from being evaluated.
Keywords: vitamin D; menopause; locomotor activity; gardening